MENAKAR MASALAH DAN TANTANGAN ADMINISTRASI PAJAK: KEPATUHAN PAJAK DI ERA SELF-ASSESSMENT SYSTEM - Liyana, Nur Farida (Jurnal Pajak dan Keuangan Negara (PKN), 2019)
Tax compliance is a major problem that needs to get more attention in the era of self assessment system. Many factors cause low taxpayer compliance. Trust in tax institutions, complicated regulations, low public awareness and tax administration are the main issues affecting taxpayer compliance in Indonesia. Organizational improvement, human resources, information technology, business processes and legislation are expected to be able to overcome the problems of tax administration so that it will improve taxpayer compliance. In addition, changes in people's perspectives need to be continued, excellent service and organizational transparency need to be carried out by the Directorate General of Taxes. Education of taxpayers needs to be improved to improve tax compliance and channeling payments and reporting needs to continue to be a new effort in this era of information technology. Finally, collaboration with all government and private agencies is a complement to raising tax awareness so that voluntary compliance can be achieved.